CORPORATE GOVERNANCE - ITS STANDARDS AND ORGANIZATIONAL DIMENSIONS: AN EXPLORATORY STUDY OF SOME INTERNATIONAL EXPERIENCES IN THE APPLICATION OF GOVERNANCE STANDARDS AND DIMENSIONS - Sattar Oleiwi Dahash (Scholars Digest Publishing, 2024)
The application of good governance rules is of great importance to public and private sector institutions, especially for companies listed in the financial markets, as they constitute an important element of the company's evaluation, and a reassuring factor for investors, which leads to gaining the confidence of dealers in the financial market. Investment managers have also become professionals who take the extent to which joint stock companies apply governance rules as a value added to the company's share, if not to say that they have a significant role in making an investment decision or not in a particular company, not only that, but governance rules have become one of the standards on which public sector institutions as well as the private sector rely. Therefore, this research is exposed to the concept of governance and its organizational aspects by referring to some international experiences in the application of governance.
Keywords: Governance – Organizational Dimensions – Companies – Governance Stakeholders.